Analisis Keunggulan Komparatif Sektor Peternakan Di Kabupaten Hulu Sungai Utara - Heldawati Heldawati; Siti Maisyarah (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2017)
This study aims to discuss the application of Location Quotient (LQ) method in identifying superior commodities of livestock sector of each sub-district in Hulu Sungai Utara Regency. The research method used is descriptive quantitative research method, the data collected in this research is secondary data, this research will identify and analyze superior commodity sector or livestock base. Data analysis using Location Quotient method. The results showed that the livestock population is said to be superior or base if it meets the criteria of basic commodities. Leading commodities of the livestock sector in Hulu Sungai Utara Regency cover buffalo cattle and ducks in Paminggir District